2013
DOI: 10.1159/000354643
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Gene Network Analysis of Thyroid Transcription Factor 1 <b><i>(TTF1)</i></b> and Enhanced at Puberty <b><i>(EAP1)</i></b> Genes in Patients with GnRH-Dependent Pubertal Disorders

Abstract: Background/Aim: TTF1 and EAP1 are transcription factors that modulate gonadotropin-releasing hormone expression. We investigated the contribution of TTF1 and EAP1 genes to central pubertal disorders. Patients and Methods: 133 patients with central pubertal disorders were studied: 86 with central precocious puberty and 47 with normosmic isolated hypogonadotropic hypogonadism. The coding region of TTF1 and EAP1 were sequenced. Variations of polyglutamine and polyalanine repeats in EAP1 were analyzed by GeneScan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 49 publications
0
11
0
1
Order By: Relevance
“…Although these case reports expanded the genotype-phenotype correlations for the kisspeptin pathways, no other CPP cases with gain-of-function mutations in KISS1R or KISS1 have been reported, suggesting that these genetic abnormalities are very rare. Other candidate genes implicated in the regulatory mechanism of GnRH secretion have also been screened (GABRA1 , NPY-Y1R , LIN28B, TAC3 , TACR3, TTF1 and EAP1) , but no pathogenic variants were identified until recently [24,25,26,27,28]. …”
Section: Rare Gain-of-function Mutations In Kiss1 and Kiss1rmentioning
confidence: 99%
“…Although these case reports expanded the genotype-phenotype correlations for the kisspeptin pathways, no other CPP cases with gain-of-function mutations in KISS1R or KISS1 have been reported, suggesting that these genetic abnormalities are very rare. Other candidate genes implicated in the regulatory mechanism of GnRH secretion have also been screened (GABRA1 , NPY-Y1R , LIN28B, TAC3 , TACR3, TTF1 and EAP1) , but no pathogenic variants were identified until recently [24,25,26,27,28]. …”
Section: Rare Gain-of-function Mutations In Kiss1 and Kiss1rmentioning
confidence: 99%
“…Recent evidence shows that this intercellular mechanism of excitatory vs inhibitory balance is mirrored at the genomic level. Three gene groups have emerged: as either PI genes (eg, GAD67 , PDYN , GnIH ), PA genes (eg, GnRH , GLS , KISS1 , TTF1 ) or genes with dual effects depending on hormonal milieu and cell identity (eg, TAC3 , EAP1 ).…”
Section: Neuroendocrine Regulation Of Puberty: Neuronal Circuits Gnrmentioning
confidence: 99%
“…This SNP was near the TTF1 locus, known as Nkx2.1. 84 Moreover, network connectivity analysis showed that TTF1 and EAP1 serve as central hubs to a number of genes associated with menarche, [85][86][87] including GAB2, NR4A2, ZNF462, ZNF483, TMEM18, PAX8, KDM3B, KISS1 and KISS1R (an extended gene list is provided elsewhere 69 ). These menarche-related genes are connected to two or more TRG central nodes as determined by genemania network software 88 and available databases.…”
Section: Decod Ing Pub Ertal G Ene Ne T Wo Rk Smentioning
confidence: 99%
“…Genomic DNA was extracted from peripheral blood leukocytes using the Gentra Puregene Blood Kit (Qiagen, Hilden, Germany). A targeted panel was designed using 69 genes that were known to be involved in hypothalamus/pituitary development [15][16][17][18][19][20][21][22][23], GnRH neuronal migration [10,11,[24][25][26][27][28][29][30][31][32][33][34], synthesis and secretion of GnRH [35][36][37][38][39][40][41][42], IGD associated neurological disorders [43][44][45][46][47][48], and rare syndromes [26,30,[49][50][51][52][53][54][55][56][57] associated with hypogonadism ( Table 1S, Supporting Information). For compreh...…”
Section: Targeted Gene Panel Sequencing and Bioinformatics Analysismentioning
confidence: 99%